THEORETICAL APPROACHES TO THE STUDY OF EMOTIONAL INTELLIGENCE IN PSYCHOLOGY - Marchyk, Snizhana (Personality and environmental issues, 2026)
The article is devoted to the theoretical analysis of the concept of emotional intelligence. Various reviews of theoretical approaches to the study of emotional intelligence among foreign and domestic scientists are presented. Particular attention is paid to foreign concepts in the understanding of emotional intelligence, its common and different positions on the structure and genesis of development, because the beginning of research on this concept was laid by foreign scientists. Much attention is paid to the problem of the urgency of insufficient study of emotional intelligence and its impact on the individual at the present stage of development of society. The expediency of the study of emotional intelligence at the present stage of development of psychological science in Ukraine is also emphasized. It is proved that the problem of emotional intelligence is not new in the Ukrainian scientific literature, and the need to study emotional intelligence requires a deeper analysis of this concept at the present stage of development of science. The article also describes the first theoretical and empirical studies of emotional intelligence. The article analyzes and describes the views of various scientists on the classification of emotional intelligence throughout the history of the study of this concept. The article describes the concept of emotional intelligence as foreign and domestic scientists throughout the period of development of psychological science. At the same time, studies of the phenomenon of emotional intelligence have led to the development of ideas about the relationship of cognitive and affective processes. The theoretical analysis of the scientific literature indicates that in modern psychological science there is a problem of multiple concepts and definitions of emotional intelligence. It is proved that there is no consensus among scientists on understanding the essence of emotional intelligence, despite the large amount of research over time. For successful formation and development it is necessary to understand what is behind this concept, so the presented material considers a variety of theoretical approaches to the study of emotional intelligence. Prospects for further research are a more detailed empirical study of the impact of emotional intelligence on various areas of life.